2019
DOI: 10.1038/s41598-019-52655-y
|View full text |Cite
|
Sign up to set email alerts
|

Direct, gabapentin-insensitive interaction of a soluble form of the calcium channel subunit α2δ-1 with thrombospondin-4

Abstract: The α2δ‐1 subunit of voltage-gated calcium channels binds to gabapentin and pregabalin, mediating the analgesic action of these drugs against neuropathic pain. Extracellular matrix proteins from the thrombospondin (TSP) family have been identified as ligands of α2δ‐1 in the CNS. This interaction was found to be crucial for excitatory synaptogenesis and neuronal sensitisation which in turn can be inhibited by gabapentin, suggesting a potential role in the pathogenesis of neuropathic pain. Here, we provide infor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 74 publications
0
9
0
Order By: Relevance
“…More recently, another study 37 showed a weak interaction between α 2 δ-1 and TSP4, but was unable to demonstrate any interaction between cell-surface expressed α 2 δ-1 and TSP4, concluding that α 2 δ-1 and TSP4 may only interact intracellularly at high concentrations. A further study showed a low affinity interaction between α 2 δ-1 and TSP4, but not other TSPs 38 . However, any interaction of α 2 δ subunits with TSPs is unlikely to be involved in their Rab11-dependent recycling.…”
Section: Discussionmentioning
confidence: 83%
“…More recently, another study 37 showed a weak interaction between α 2 δ-1 and TSP4, but was unable to demonstrate any interaction between cell-surface expressed α 2 δ-1 and TSP4, concluding that α 2 δ-1 and TSP4 may only interact intracellularly at high concentrations. A further study showed a low affinity interaction between α 2 δ-1 and TSP4, but not other TSPs 38 . However, any interaction of α 2 δ subunits with TSPs is unlikely to be involved in their Rab11-dependent recycling.…”
Section: Discussionmentioning
confidence: 83%
“…However, two separate studies have failed to show that gabapentin directly disrupts the molecular interaction between thrombospondin and 2-1 proteins in vitro (Lana et al, 2016;El-Awaad et al, 2019), suggesting that the inhibition by gabapentin of thrombospondin actions could be indirect or require the presence of other proteins. Additional studies suggest that signaling proteins, including the scaffolding protein LRP1 (Kadurin et al, 2017) or activation of the small Rho GTPase, Ras-related C3 botulinum toxin substrate 1 (Rac1) are part of the biochemical pathway involved in the synaptogenic action that is inhibited by gabapentinoid drugs (Risher et al, 2018).…”
Section: Jpet # 266056 Page 19mentioning
confidence: 99%
“…More recently, another study (Lana et al, 2016) showed a weak interaction between α 2 δ-1 and TSP4, but was unable to demonstrate any interaction between cell-surface expressed α 2 δ-1 and TSP4 nor were they able to demonstrate the importance of the EGF domains of TSP4 in this interaction, concluding that α 2 δ-1 and TSP4 may only interact intracellularly at high concentrations. A further study showed a low affinity interaction between α 2 δ-1 and TSP4, but not other TSPs, which was gabapentin-insensitive and did not involve the EGF domain of TSP4 (El-Awaad et al, 2019). However, any interaction of α 2 δ subunits with TSPs is unlikely to be involved in their Rab11-dependent recycling.…”
Section: Discussionmentioning
confidence: 99%